2015
DOI: 10.1111/jgh.13067
|View full text |Cite
|
Sign up to set email alerts
|

Combination of EUS‐FNA and elastography (strain ratio) to exclude malignant solid pancreatic lesions: A prospective single‐blinded study

Abstract: In this prospective single-blinded study, the negative results of both EUS-FNA and SR were more reliable to exclude malignant SPL. The sensitivity of EUS elastography by SR was not superior to EUS-FNA. © 2015 Journal of Gastroenterology and Hepatology Foundation and Wiley Publishing Asia Pty Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
(76 reference statements)
8
17
0
1
Order By: Relevance
“…Computer-aided diagnosis techniques might improve the accuracy for the differential diagnosis of focal pancreatic masses, with artificial neural networks being used most often [154,156]. Several multicenter studies [155,156,194] and other prospective studies [135,149,150,152,177,197,198] consistently showed a very high sensitivity (over 90 %), but considerably lower specificity and negative predictive values for the diagnosis of benign versus malignant focal pancreatic masses. These findings have been summarized in meta-analyses, affirming the very high sensitivity (95 % -99 %) and negative predictive value of EUS-SE, but limited specificity (64 % -76 %) and positive predictive value to diagnose pancreatic malignancy [172, 189 -192].…”
Section: Pancreatic Ductal Adenocarcinoma and Other Solid Pancreatic mentioning
confidence: 99%
“…Computer-aided diagnosis techniques might improve the accuracy for the differential diagnosis of focal pancreatic masses, with artificial neural networks being used most often [154,156]. Several multicenter studies [155,156,194] and other prospective studies [135,149,150,152,177,197,198] consistently showed a very high sensitivity (over 90 %), but considerably lower specificity and negative predictive values for the diagnosis of benign versus malignant focal pancreatic masses. These findings have been summarized in meta-analyses, affirming the very high sensitivity (95 % -99 %) and negative predictive value of EUS-SE, but limited specificity (64 % -76 %) and positive predictive value to diagnose pancreatic malignancy [172, 189 -192].…”
Section: Pancreatic Ductal Adenocarcinoma and Other Solid Pancreatic mentioning
confidence: 99%
“…It has been identified as a sensitive modality to assist with the diagnosis of PDAC during EUS-guided FNA, but is presently limited by poor specificity. 11,21 Similarly, RNA sequencing has been shown to distinguish malignant from benign lesions with high sensitivity (87%) but lower specificity (75%). In addition, there was inadequate RNA in 9 of the 48 enrolled subjects, limiting this adjunct in a similar way to cytopathology.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Elastography, fluorescence in situ hybridization, K-RAS analysis, microRNAs, immunostaining, and RNA-sequencing analysis have all been proposed as supplementary tests to cytopathology, but none have gained widespread use. [11][12][13][14] Here, we explore the inflammatory milieu of the PDAC microenvironment as a potential diagnostic supplement to cytopathology. Desmoplastic stroma represents as much as 80% of the overall PDAC tumor volume.…”
mentioning
confidence: 99%
“…Elastography can be used to evaluate tissue stiffness and to assess the elasticity of solid lesions. Some studies have shown that EUS guided elastography is useful in improving diagnostic yield and efficiency of EUS-FNA of solid pancreatic lesions, however, this remains controversial [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%